Respuesta :
Answer:
-5
Step-by-step explanation:
The answer is -5 because we have -2 as x. The function is h(x)=3x+1. 3 times -2=-6. When we add 1 to the result, we have -5 as the answer. Hope it helps!
The value of h(−2) when h(x)=3x+1 is h(-2) = -5
From the question,
The given function is h(x)=3x+1
To determine the value of h(-2), we will put x = -2 and evaluate
From
h(x)=3x+1
h(-2) becomes
h(-2)=3(-2) + 1
h(-2) = (3× -2) + 1
h(-2) = (-6) + 1
h(-2) = -6 + 1
h(-2) = -5
Hence, the value of h(−2) when h(x)=3x+1 is h(-2) = -5
Learn more here: https://brainly.com/question/17762942